A novel calix[4]arene-modified porphyrin-based dual-mode sensor for the specific detection of dopamine with excellent performance. (13th June 2019) - Liu, Qi; Dong, Jurong; Sun, Qiqi; Zhao, Shuai; Chen, Yanli; Jiang, Jianzhuang
Abstract : A dual-mode sensor for dopamine with remarkable specificity is developed based on a novel calix[4]arene-functionalized porphyrin derivative. Abstract : A novel calix[4]arene-functionalized porphyrin derivative H2 T[(C4AP)(Pyr)3 ]P (1 ) has been designed, synthesized and characterized. A combination of the effective molecular recognition/enrichment and good optoelectronic properties derived from calix[4]arene and pyrene substituents as well as the π-conjugated porphyrin skeleton leads to the fluorometric and voltammetric dual-mode sensing activity of1 for DA in the range of 1–50 μM and 2–100 μM, respectively, with remarkable specificity, representing the first multi-modal molecular sensor for DA.